Optimal Tempo for Groove: Its Relation to Directions of Body Movement and Japanese nori - Etani, Takahide; Marui, Atsushi; Kawase, Satoshi; Keller, Peter E. (Frontiers in Psychology, 2018)
The tendency for groove-based music to induce body movements has been linked to multiple acoustical factors. However, it is unclear how or whether tempo affects groove, although tempo significantly affects other of aspects of music perception. To address this issue, the present study investigated effects of tempo, specific rhythmic organizations of patterns, and syncopation on groove and the induction of the sensation of wanting to move. We focused on the directions of body movement in particular by taking into account nori, which is an indigenous Japanese musical term used not only synonymously with groove, but also as a spatial metaphor indicating vertical or horizontal directions. Thus, the present study explored how groove was felt and defined, as well as how musical factors induced sensation of wanting to move in cross-cultural context. A listening experiment was conducted using drum breaks as stimuli. Stimuli consisted of various rhythm patterns at six tempi from 60 to 200 BPM. The main findings are that: (1) an optimal tempo for groove existed for drum breaks at around 100–120 BPM, (2) an optimal tempo existed for the sensation of wanting to move the body in specific directions (i.e. back-and-forth and side-to-side), (3) groove and nori shared a similar concept of wanting to move but differed on several points (i.e. association with sense of pulse and fast tempo). Overall, the present study suggests that there is an optimal tempo for body movement related to groove. This finding has implications for the use of music or rhythmic stimuli to induce smooth motion in rehabilitation, therapy or dance.